PENGARUH SIKAP PERCAYA DIRI SANTRIWATI KELAS 6 KMI TERHADAP PEMBELAJARAN MICRO TEACHING (AMLIYAH AT-TADRIS) DI PONDOK PESANTREN MAWARIDUSSALAM BATANG KUIS DELI SERDANG - Azizah; Yurmaini; Fitri Yulia (STKIP Subang, 2026)
Educational management is a process of planning, organizing, controlling, and evaluating educational activities that have been designed to achieve predetermined educational goals effectively and efficiently. Kulliyatul Mu’allimat alIslamiyyah (KMI) education at Mawaridussalam Islamic Boarding School aims to produce pious and multi-talented female students in various fields. This study aims to determine the extent to which self-confidence attitudes of sixth-year female students in the KMI program influence the success of microteaching (Amaliyah AtTadris) learning at Pondok Pesantren Mawaridussalam. A quantitative correlational approach was employed. The research population consisted of 109 sixth-year KMI students, from which a sample of 40 students was selected using simple random sampling. Research instruments included a self-confidence questionnaire that had been tested for validity and reliability with a Cronbach’s alpha value of 0.90, as well as a rubric for assessing microteaching performance. Before conducting the main analysis, the data were tested using prerequisite tests, including normality testing with the Kolmogorov–Smirnov test (p > 0.05), linearity testing using regression line ANOVA (p < 0.05), and homoscedasticity testing using the Glejser test (p > 0.05). All test results met the required criteria. Hypothesis testing using Pearson’s correlation analysis produced a correlation coefficient of r = 0.65 with a significance value of p = 0.000 (p < 0.05), indicating a positive and significant relationship between self-confidence attitudes and microteaching success. In other words, higher levels of self-confidence among students are associated with better performance in Amaliyah At-Tadris. These findings highlight the importance of strengthening students’ self-confidence through pre-microteaching training, psychological support, and emotional mentoring in order to optimize the microteaching learning process and improve teaching quality.